From Words to Actions: Exploring How e-WOM Drives Green Consumer Decisions in the Digital Age - Waskita, Gautama Sastra; Ashari, Denny Rakhmad Widi; Eldon, Mokhamad; Utami, Artanty (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
In the digital age, electronic word-of-mouth (e-WOM) has emerged as a pivotal factor influencing green consumer behavior and repurchase intentions. However, the role of e-WOM in shaping sustainable purchase decisions remains underexplored, especially in the context of the green brands. This study aims to explore how e-WOM impacts consumer perceptions of green brands and the factors that drive sustainable purchasing decisions. Using an autoethnographic approach, the research reflects on personal experiences with e-WOM and examines its influence on green consumer behavior. The findings reveal that e-WOM not only provides valuable information but also fosters emotional engagement, trust, and social influence, which play a significant role in driving both initial purchases and long-term repurchase intentions. This study highlights the need for businesses to incorporate authentic e-WOM strategies into their green marketing efforts, focusing on transparency and consumer trust. The results offer practical insights for marketers seeking to leverage digital platforms in promoting sustainable products while also contributing to the broader theoretical understanding of sustainable consumer behavior. Future research could explore the long-term impact of e-WOM and examine its role across diverse cultural contexts.